1997
DOI: 10.1577/1548-8640(1997)059<0161:acoeas>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Articles: Characteristics of Effluent and Sludge from Two Commercial Rainbow Trout Farms in Minnesota

Abstract: Waste loads resulting from groundwater‐fed raceway production of rainbow trout Oncorhynchus mykiss at two commercial trout farms in Minnesota were monitored. Loads of solids, organic carbon (C), and dissolved and total nitrogen (N) and phosphorus (P) were measured directly in effluent and in accumulated sludge and were normalized to fish biomass and production. Most of the observed nutrient waste (solid and dissolved) and about half of the observed solids load were present in the effluent fraction. Total annua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 10 publications
(18 reference statements)
1
10
1
Order By: Relevance
“…The calculated nutrient loading of this study ( Table 1) is similar to data obtained by other authors. It lies within the range of values observed by Axler et al [15] for trout farming: 47-87 g N kg À1 of fish and 4.8-18.7 g P kg À1 of fish. For turbot, our results are higher than those of Mallekh et al [10] (51 g N kg À1 of fish and 8.7 g P kg À1 of fish), probably because their study was conducted in tanks, which induced a low FCR (0.96).…”
Section: Feeds and Their Managementsupporting
confidence: 84%
“…The calculated nutrient loading of this study ( Table 1) is similar to data obtained by other authors. It lies within the range of values observed by Axler et al [15] for trout farming: 47-87 g N kg À1 of fish and 4.8-18.7 g P kg À1 of fish. For turbot, our results are higher than those of Mallekh et al [10] (51 g N kg À1 of fish and 8.7 g P kg À1 of fish), probably because their study was conducted in tanks, which induced a low FCR (0.96).…”
Section: Feeds and Their Managementsupporting
confidence: 84%
“…This factor is less important for dissolved compounds than for suspended fractions, which experiences much heterogeneity in its concentration in the water column. This is especially the case for aggregates of faeces or uneaten feed which are released at variable intervals by fish farms and are difficult to measure using standard sampling methods, as previously shown by different authors (Cripps 1995;Axler et al 1997;Cripps and Bergheim 2000;Maillard et al 2005;Roque d'Orbcastel et al 2008). The capture of these suspended solids, which pass sporadically into the effluent, is therefore difficult using automatic samplers that take only one sample per hour.…”
Section: Discussionmentioning
confidence: 99%
“…No correlation between the assessment methods was found for suspended solid emissions, and the data set does not allow us to conclude that one of the assessment methods is more robust than the other, due to the variety of sources of uncertainty associated with each of them (e.g., sampling, hydraulics, farm management). However, Axler et al (1997) reported that only half of the solids produced within two trout farms were collected in their effluent water. Cho et al (1991), who faced the same problem, were more confident about results of the massbalance modelling method than those of the hydrological approach due to the latter's sampling bias.…”
Section: Discussionmentioning
confidence: 99%
“…Sindilariu 2007) and the effluent water quality is highly affected by farm management practices such as stocked fish size, stocking density, feed quality, feeding techniques, frequency of cleaning, etc., as well as temporal variations such as influent water quality and flow rate (e.g. Axler et al 1997). Ammonia nitrogen can form 53 to 69% of total nitrogen wastes in the effluent of rainbow trout farms (Kajimura et al 2004), but the ratio may increase up to 79% in some in stances (Dalsgaard & Pedersen 2011).…”
Section: Effluent Characteristicsmentioning
confidence: 99%